Singapore’s tuition scene : the evaluation between internal and external driving factors. - Chong, Bi Xuan. (2013)
This study aims to investigate the internal and external driving factors affecting their decision to attend tuition and their effect on their willingness to attend tuition. A total of 3 hypotheses were formulated based on the literature that we have found. Data collection was done through quota and snowball sampling, using self-administered online survey on Qualtrics.com. After data cleaning and preparation, 153 completed questionnaires were used for data analysis.